Bhesa xieii (Centroplacaceae), a new species from Guangxi, China - Jiang, Ri-Hong; Lin, Jian-Yong; Zhu, Chang-San; Liu, Xiu; Tang, Li-Ming; An, Jia-Cheng (Phytotaxa, 2022)
Bhesa xieii, a new species of Centroplacaceae from southern China, is described and illustrated. Morphological comparison with Bhesa robusta, B. paniculata and B. ceylanica is provided. Both morphological and molecular evidences clearly indicate that B. xieii is a distinct species. It differs in capsules narrowly ovate, ca. 3 cm long, apex obtuse, peduncle thick, ca. 3 mm long; racemes; flowers pale yellow, pedicels 1.5–2.5 mm long; calyx lobes broadly ovate to subrotundate, apex obtuse; petals ovate to oblong-elliptic, apex obtuse, inflexed; lamina oblong-elliptic to narrowly ovate, base obtuse or subtruncate, apex acute or obtuse.